Pelatihan dan Pendampingan Pemahaman Literasi Digital bagi Siswa MI Darussalam Sumber Rejo Kecamatan Paiton - Listrianti, Feriska; Paramita, Agustin Septia; Dewi, Ninda Ayu Rosyidah; Taqiyah, Albarratut; Aisah, Siti; Lailiyah, Nurul (Al-DYAS, 2024)
Madrasah Ibtidaiyah (MI) Darussalam Paiton faces challenges in utilizing digital technology in the learning process due to limited facilities and low digital literacy among students and teachers. This issue affects the optimal use of technology as a learning tool and the lack of parental support for technology-based education at home. To address these challenges, a community service program was implemented, consisting of digital literacy training and mentoring for MI Darussalam’s students and teachers. The program included training on the use of technology devices, integration of technology in learning, and socialization for parents on the importance of digital literacy. The results of this program showed a significant improvement in students' digital literacy understanding, teachers' ability to integrate technology into teaching, and increased awareness and support from parents. However, some students and parents still require additional assistance. Based on these findings, it is recommended that further training programs and increased access to technological resources at school and home be pursued to ensure the sustainability of the program.